If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -2x = g Solving 4 + -2x = g Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -2x = -4 + g Combine like terms: 4 + -4 = 0 0 + -2x = -4 + g -2x = -4 + g Divide each side by '-2'. x = 2 + -0.5g Simplifying x = 2 + -0.5g
| 4a+6b-12=0 | | 2.32+.23x=5.25 | | 3w-(-12)=7 | | 3(7x-(6-5y+5x)+4y)= | | 0.5x-0.4x-2=70-3.5x | | 48x^2+96x=0 | | 3x^2(2x^2+5)= | | x^2-9x=-13 | | 4x-6=10-2(x-1) | | 3x^2+42x=150 | | (6x+7)(7x-6)=0 | | -13.00+2.00=11 | | 2x^2-8x=7 | | 0.01-0.01(x+1)=-0.03(4-x) | | 2x=-2x^2+4 | | 3x-2x+4-x+x=60 | | 2x^2-7x=-4 | | -4x=-2x^2+30 | | 7-2x=11-6x | | 3x=577 | | 2x^2-7x=8 | | -6+4=40 | | 0=4x^3-56x | | 5x=11x+4 | | 20x+8=-8x^2 | | (x-10)2/5=(9x)1/5 | | 2x^2-11x=-2 | | 8w-13=3 | | 2-2x^3+4x^2-x=0 | | 3n-14=1 | | 3x^2-3x=3 | | -10x=-4x^2+24 |